Maturity Level of Production and Logistics Digitalization in Automotive Companies - Mirosław MATUSEK (Communications of International Proceedings, 2021)
The aim of the paper is the assessment of the maturity level of the implementation of Industry 4.0 solutions in production and logistics subsystems in automotive industry companies located in Poland. The automotive sector is one of the key branches of the global economy. Automotive is also a very important sector of the Polish economy, as it generates over 8% of GDP and accounts for over 20% of the annual export value. Industry 4.0. and effective use of modern technologies gives a chance for its further dynamic development. However, the literature lacks sufficient understanding of the maturity level of digitalization of production and logistics processes of automotive suppliers located in Poland. Maturity assessment is not only a diagnosis of the existing state, but also an indication of the directions of further efforts towards full digitalization of business processes. Based on a sample of 50 respondents representing 50 companies from the automotive industry located in Poland (including 34 large, 12 medium sized and 4 small companies) the research allowed answering the questions whether the level of maturity of digitalization of production and logistics subsystems in automotive companies differs depending on their size and their place in the value chain.
Keywords: Industry 4.0; Automotive; Manufacturing; Logistics; Maturity Model; Value Chain.